Pelangaran Lalu Lintas Oleh Anak Dibawah Umur di Jalan Tunjungan Surabaya - Rizki Agustina; Agus Machfudz Fauzi (Jurnal Hukum Sasana, 2022)
Some of the problems are from the types of violations that exist, not a few of the perpetrators are minors who drive motorized vehicles. Many teenagers are not supposed to bring their own motorized vehicle and ironically this problem is coupled with the rider not wearing a safety helmet. Law enforcement for underage two-wheeled vehicle drivers without a driving license has been stipulated in Law No. 22 of 2009 concerning Road Traffic and Transportation. The purpose of this study is to find out what the reasons are that minors continue to drive two-wheeled vehicles even though they already know that it is a traffic violation. In this study, a descriptive qualitative approach was used. Based on the results of the study, the reason why minors continue to drive two-wheeled vehicles on the highway is because of the weak supervision by parents and freedom from parents, as well as the lack of knowledge and understanding of the community, especially children who are still underage.